The Efficacy and Safety of First-Line Chemotherapy in Patients With Non-small Cell Lung Cancer and Interstitial Lung Disease: A Systematic Review and Meta-Analysis - Wang, Yanning; Miao, Liyun; Hu, Yuxuan; Zhou, Yujie (Frontiers in Oncology, 2020)
Background: Lung cancer is a well-known comorbidity of interstitial lung disease (ILD), and the actual efficacy and safety of chemotherapy for patients with non-small cell lung cancer and interstitial lung disease (NSCLC-ILD) have not been determined. We conducted this meta-analysis to assess the efficacy and safety of chemotherapy for patients with NSCLC-ILD. Methods: We searched related studies from the Cochrane Library, PubMed, and Embase. The endpoints were objective response rate (ORR), disease control rate (DCR), 1-year overall survival rate (1-yOS rate), and first-line chemotherapy-related acute exacerbation of interstitial lung disease rate (AE-ILD rate). Results: We included 21 studies involving 684 patients in our analysis. The pooled ORR was 43% (95% CI: 38.0–49.0%), and the pooled DCR was 80.0% (95% CI: 75.7–83.9%). The modified overall 1-yOS rate was 33.0% (95% CI: 29.0–37.0%). The pooled AE-ILD rate was 8.07% (95% CI: 6.12–10.26%). Subgroup analysis revealed a trend for lower AE-ILD rate (4.98%; 95% CI: 2.44–8.37%) in patients with carboplatin plus nab-paclitaxel. Lung function and AE-ILD may be associated with the prognosis of patients with NSCLC-ILD. Conclusions: First-line chemotherapy is effective in patients with NSCLC-ILD, and the AE-ILD rate is acceptable, but the prognosis is limited. Future randomized controlled trials are needed to explore more appropriate treatment regimens to improve the prognosis of patients with NSCLC-ILD.